Characterizing the Thin-Film Response of Metal Phthalocyanine-Based OTFT Cannabinoid Sensors - Lamontagne, Halynne (Université d'Ottawa / University of Ottawa, 2025)
Metal phthalocyanine (MPc)-based organic thin-film transistors (OTFTs) provide a potentially cost-effective solution to cannabis consumers, producers and regulators alike to detect and speciate Δ⁹-tetrahydrocannabinol (THC) and cannabidiol (CBD) in both solution and vapor cannabis samples. This sensing response is driven by unique coordinating interactions with MPcs and cannabinoids in solution and thin films which cause a change in the device performance upon exposure. This thesis looked to further characterize and understand these interactions to inform optimization efforts for OTFT sensors using multiple approaches, including optimization of the channel and device architecture, and molecular tuning. Through the integration of device performance data and physical characterization techniques such as atomic force microscopy (AFM), grazing incidence wide-angle X-ray scattering (GIWAXS), and Raman spectroscopy, the interactions between cannabinoids and thin films of MPcs can be characterized and correlated to improved performance. Firstly, I investigated the effect of channel dimension and film thickness on the response of chloro aluminum phthalocyanine (Cl-AlPc) based OTFT sensors, where the film roughness and thickness were found to have the greatest influence on the sensing response. Following, I performed a series of axial phenoxylations to improve the performance of R-AlPc in OTFT cannabinoid sensors. The phenoxy-AlPc compounds were found to adopt different thin film motifs from Cl-AlPc that made them more responsive to THC and/or CBD. Finally, I investigated the sensing response of the air-stable, n-type molecule (F₅PhO)₂-F₁₆-SiPc to expand our library of sensing molecules and further studied its thin film structure. In this case, substitution of the hydrogen atoms with fluorines was detrimental to its sensing response. I conclude this thesis with my additional work on other projects related to thin film characterization, physical vapor deposition, and sensor integration in our group, and detail how my expertise has shaped our lab’s knowledge on structure-property relationships of a variety of materials. As the push for the commercialization of OTFTs and OTFT-based sensors continues, establishing an understanding of the thin film and electronic properties of a range of materials remains essential.
Keywords: OTFTs; sensors; phthalocyanines; thin film characterization; cannabinoids